Studies on the fibrinolytic enzyme system in obesity - Bennett, N. B. (1966)
Plasma fibrinolytic activity, inhibitors of fibrinolysis, and fibrinogen were estimated in 34 subjects of varying ratio of observed to standard weight. The inverse relationship between fibrinolytic activity and the ratio of observed to standard weight was confirmed. No significant correlation was found between anti-plasmin or anti-urokinase and the ratio of observed to standard weight. It was therefore concluded that the decreased plasma fibrinolytic activity in obese subjects is due to decreased production of plasminogen activator rather than to excessive inhibition.